PENERAPAN PERMAINAN TEBAK KATA “SIAPA AKU” UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS II SDN 3 BUARAN - Nurismail, Budi; Eka Zuliana; Lintang Kironoratri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low reading comprehension ability of elementary school students, particularly second-grade students at SDN 3 Buaran. Students still experienced difficulties in understanding the content of reading texts and answering questions based on the texts they read. This study aimed to determine the effect of implementing the “Who Am I” word-guessing game on students’ reading comprehension skills. This research employed a quantitative approach with a pre-experimental one-group pretest–posttest design. The population as well as the sample consisted of all second-grade students of SDN 3 Buaran in the 2025/2026 academic year, totaling 19 students. Data were collected using pretest and posttest assessments. The research instruments were validated through expert judgment. Data analysis was conducted using the Shapiro–Wilk normality test and hypothesis testing with a paired sample t-test. The results showed that there was a significant difference between the pretest and posttest scores. This was evidenced by a significance value (2-tailed) of 0.000 < 0.05 and a t-value of -9.273. The average improvement in learning outcomes was categorized as high. Therefore, the implementation of the “Who Am I” word-guessing game is effective in improving the reading comprehension skills of second-grade students at SDN 3 Buaran.